Maternal and newborn outcomes at a tertiary care hospital in Lusaka, Zambia, 2008–2012. Issue 2 (24th November 2016) - Vwalika, Bellington; Stoner, Marie C.D.; Mwanahamuntu, Mulindi; Liu, K. Cherry; Kaunda, Eugene; Tshuma, Getrude G.; Somwe, Somwe W.; Ahmed, Yusuf; Stringer, Elizabeth M.; Stringer, Jeffrey S.A.; Chi, Benjamin H.
Abstract: Objective: To measure key obstetric and neonatal outcomes recorded at a tertiary hospital in Zambia over a 5‐year period. Methods: A retrospective analysis was conducted among women who had delivered at the University Teaching Hospital in Lusaka, between January 1, 2008, and December 31, 2012. Data were extracted from electronic medical records. The main outcomes were maternal mortality, cesarean delivery, prenatal or intrapartum hemorrhage, stillbirth, a 5‐minute Apgar score of less than 7, and admission to the neonatal intensive care unit. Results: A total of 62 470 deliveries were recorded. Rates of maternal mortality, cesarean delivery, and hemorrhage during pregnancy all declined over time. Decreased admissions to the neonatal intensive care unit were observed; however, the rate spiked temporarily in late 2011 and early 2012 before returning to previous levels. The proportion of stillbirths remained stable over time but reports of a 5‐minute Apgar score of less than 7 rose. Conclusion: Routinely collected obstetric and neonatal data could aid ongoing program monitoring and should be used to guide quality improvement activities. Abstract : Declines in several adverse pregnancy outcomes — including maternal mortality—were observed in a tertiary care setting in Lusaka, Zambia, from 2008 to 2012.